Malakoplakia of the adrenal gland. Issue 6 (June 1981) - Benjamin, E; Fox, H
Abstract : The clinical and pathological features of a case of malakoplakia of the adrenal gland occurring in a woman with Escherichia coli infection are described. This lesion mimicked a neoplasm, the true diagnosis only being revealed by histological examination. The light and electron microscopic features are described and it is suggested that malakoplakia is due to an abnormal macrophage response to E coli infection.